THE STUDY OF IMPLICATURE USED BY THE HOST AND JAYA SUPRANA IN ”KICK ANDY SHOW”;KELIRUMOLOGIEPISODE - HIDAYAT, FADIL MUHTAD (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: implicature, Kick Andy Show, kelirumologi Consciously or not, ideal communication does not always happen in conversation. It may lead to what is called implicature. In this study, the researcher conducted a study about Implicature in Kick Andy Show, specifically on Kelirumologi episode that reveals its occurrence in the interview. The researcher uses Grice’s theory which reveals the implicit meaning found in the conversation. There are two problems in the study which need to be unraveled, those are : (1) What are the types of implicatures used in the interview between Andy F. Noya and Jaya Suprana in Kick Andy show? (2) How are the implicatures used in the interview between Andy F. Noya and Jaya Suprana inKick Andy show?This study uses descriptive qualitative method as it describes the phenomena of language that is used in the current interview. It is a qualitative study since the data are in the forms of sentences which are not statistically analyzed and directed toward determining the nature of situation, as it exists at the time of study. Qualitative study assumes that reality is socially constructed through individual or collective definitions of a situation.This study discovers that there are nineteen statements conveying implicature voiced by Andy and Jaya Supranadivided into two categories of conversational implicature; Generalized Conversational Implicature and Particularized Conversational Implicature. On its findings, implicature is often used by Andy F. Noya and Jaya Suprana as a strategy to convey implicit meaning towards audience to explain speaker’s intentions, which presents conceivable explanations of how implied meaning can be expressed by the addressee. It can be concluded that to understand particularized conversational implicature is more difficult than generalized conversational implicature. The reasons are because the hearers will (1) understand the meaning of utterance if they know the context, and (2) have background knowledge or prior knowledge.The researcher suggests the next students who intendto continue this studyto use data related to the association of Implicature and Gender by comparingimplicature used by both men and women. Next, for English Study Program toadd more references relating to this topic in order to help the next researchers intheir analysis of their study.